EFFECT OF FOLIAR APPLICATION OF GROWTH RETARDANT ON YIELD AND GERMINABILITY OF HYBRID RICE - DEVI, M. THOITHOI; VERMA, OMVATI; KRISHNA , MAYA; SEEMA (The Bioscan, 2013)
The application of gibberellic acid (GA3) increased per cent seed set from 38.3% to 48.0% in hybrid rice. This increase was due to increase in number of filled grains per panicle. Ehtrel application at different stages did not significantly influence seed yield of hybrid rice however, the highest seed yield (950 kg/ha) was recorded for GA3 application followed by ethrel application 12 days after GA3 application (925kg/ha). During storage, germination percentage in early months of storage did not changed much in all the hybrid rice treatments. Whereas after six month of storage, maximum germination of 76.0 % was recorded in the treatment where ethrel was sprayed 4, 8 and 12 days after GA3 application and lowest (52.5%) was recorded in the GA3 application treatment. Our study revealed that ethrel application following GA3 does not adversely affect seed quality and crop productivity but improved seed storability of hybrid rice.